FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERKESANAN PENGAJARAN DAN PEMBELAJARAN BAHASA ARAB SECARA DALAM TALIAN: Factors That Influenced Online Learning of Arabic Language - Binti Mahd Nayai, Siti Norhidayah; Bin Mohamed Adnan, Mohamad Azrien; Bin Mohd Salleh, Nor Hazrul (Journal of Islamic Educational Research, 2023)
This study aims to identify the factors influencing the effectiveness of online Arabic language learning. The factors involved in this study are technical support, teaching style and student readiness, administrative support, social support, and subject content. These factors were selected after being analysed using factor analysis. The respondents of this study consist of 65 Arabic language teachers from national secondary schools across the state of Kelantan. The research instrument used is a set of questionnaires containing 18 items, utilizing a Likert scale. The study’s findings were first analysed using factor analysis to identify the formed factors and subsequently analysed using descriptive statistics, comprising mean and standard deviation. The results of the factor analysis on the 18 questionnaire items revealed four factors: technical support, teaching style and student readiness, administrative support, social support, and subject content. The descriptive analysis results, using mean and standard deviation, indicated that technical support, teaching style, and student readiness are the primary factors influencing the effectiveness of online Arabic language learning. This is followed by social support, administrative support, and the last factor affecting the effectiveness of teaching and learning is the subject content.